Development of a novel 20 kV 0.1 Hz very low frequency cosine‐rectangular voltage generator for multi‐functional insulation testing of MV power cables. Issue 1 (15th December 2017) - Hou, Zhe; Li, Hongjie; Chen, Shuo; Li, Baojie; Lu, Yuxin; Ji, Shengchang
Abstract : This study covers research and development efforts to develop, design and test a novel very low frequency cosine‐rectangular voltage generator (CRVG) specialised not only for a withstand test, but also a partial discharge (PD) test of standard medium voltage (MV) cross‐linked polyethylene power cables. The system schematic and operating principle of the proposed system are presented and described. The cosinusoidal polarity reversing process is realised through L – C series resonance. A charging and discharging switch is developed by means of an insulated gate bipolar transistor series‐connected semiconductor switch. A laboratory prototype is assembled and tested. Maximum output voltage of the proposed CRVG is measured as 20 kV, which is in accordance with the expected acceptance test voltage level given in IEEE standard 400.2. Finally, the proposed system is applied to PD detection of a 300 m cable circuit with a built‐in artificial defect, and the PD locating results are presented, proving the system's feasibility.